Wheat-germ aspartate transcarbamoylase. Steady-state kinetics and stereochemistry of the binding site for L-aspartate. - Grayson, J E (1979)
1. The steady-state kinetics of the bisubstrate reaction catalysed by aspartate transcarbamoylase purified from wheat (Triticum vulgare)-germ have been studied at 25 degrees C, pH 8.5 AND I 0.10-0.12. Initial-velocity and product-inhibition results are consistent with an ordered sequential mechanism in which carbamoyl phosphate is the first substrate to bind, followed by L-aspartate, and carbamoyl aspartate is the first product to leave, followed by Pi. The order of substrate addition is supported by dead-end inhibition studies using pyrophosphate and maleate as inhibitory analogues of the substrates. Product inhibition permitted a minimum value for the dissociation constant of L-aspartate from the ternary complex to be estimated. This minimum is of the same order as the dissociation constant (Ki) of succinate. 2. A range of dicarboxy analogues of L-aspartate were tested as possible inhibitors of the enzyme. These studies suggested that L-aspartate is bound with its carboxy groups in the eclipsed configuration, and that the stereochemical constraints around the binding site are very similar to those reported for the catalytic subunit of the enzyme from Escherichia coli [Davies, Vanaman & Stark (1970) J. Biol. Chem. 245, 1175-1179].